Tingkat Kepuasan Kerja Perawat dalam Pendokumentasian Keperawatan dengan Sistem E-RM - Fitriana, Vera; Tamrin, Teguh; Cahyanti, Luluk; Yuliana, Alvi Ratna (JURNAL KESEHATAN PRIMER, 2024)
Background: Fulfilling nurse satisfaction is very important because good nursing service will affect the quality and service quality of hospital agencies. The demand for nursing services makes nursing services implement computerized-based documentation. Currently, hospitals use information technology to improve the quality of patient care by using the E-RM system. Objective: The aim of this research is to determine nurses' satisfaction in nursing documentation with the E-RM system. Method: This type of research uses an analytical survey research design with a cross sectional design, the sampling technique used is purposive sampling with a sample size of 80 respondents. The inclusion of this research were nurses who carried out nursing documentation. The data analysis technique used in this research is bivariate analysis with the chi-square test. Results: Based on the results of research that has been carried out, the majority of respondents' job satisfaction is in the satisfied category and most of the nursing documentation is in the good category.  Based on the results of statistical tests, the p value = 0.000 (α<0.05), this shows that there is a relationship between nurse satisfaction and nursing documentation with the E-RM system.